Determination of Efficiency of Trimethoprim Degradation Under UV and Persulfate Systems - Abigan, Ryan S. (Animo Repository, 2023)
Trimethoprim (TMP) as an aquatic pollutant poses ecological and human health-related risks as the antibiotic is highly soluble in water, resistant to biodegradation, and induces moderate chronic toxicity. Its prolonged presence in the environment resulted in certain bacteria strains developing antibiotic resistance. Since there is currently a relatively high wastewater residual concentration of the antibiotic, traditional wastewater treatment methods are ineffective at getting rid of it. Thus, a viable method for the removal of TMP is through Advanced Oxidation Processes (AOPs), which utilize radicals such as sulfate radicals to react with organic pollutants. As part of the study, the degradation efficiency of TMP under UV, S2O82-, and UV/S2O82- systems was determined through UV-vis spectrophotometry. It was found that the joint UV/S2O82- system degraded TMP at a relatively higher rate, averaging at a degradation efficiency of 38.61%. Moreover, the system reached a peak degradation of 53.21% during the first trial. Conversely, it was found that the UV and S2O82- systems did not show reliable and significant degradation resulting in average degradation efficiencies of 4.53% and -3.17%, respectively. Determining viable methods of degrading TMP in wastewater could benefit wastewater treatment facilities and the academic community and show improvements in global health quality.